The THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL ATTITUDE, AND INCOME ON FINANCIAL MANAGEMENT BEHAVIOR AMONG MSME ACTORS IN SIDOWUNGU VILLAGE, GRESIK REGENCY - Fitriana, Divany Ade; Takarini, Nurjanti (Management Science Research Journal, 2025)
Financial management behavior is an individual's ability to manage, which includes planning, budgeting, auditing, controlling, managing, sourcing, and storing daily financial funds. This study aims to analyze the influence of financial literacy, financial attitude, and income on financial management behavior among Micro, Small, and Medium Enterprises (MSMEs) actors in Sidowungu Village, Gresik Regency. This research uses a quantitative approach; the population in this study consists of MSME actors in Sidowungu Village, Gresik Regency. The sample used in this study consisted of 80 respondents, determined using a non-probability sampling technique with a saturated sampling method. Data were collected through questionnaire distribution and analyzed using Structural Equation Modeling (SEM) with the assistance of Partial Least Squares (PLS). Research results indicate that financial literacy, financial attitude, and income affect the financial management behavior of SMEs. There is a relationship where higher financial literacy, positive financial attitudes, and more stable income tend to lead to more orderly cash flow management, transaction recording, and effective financial planning.